Modified Diatomaceous Earth in Heparin Recovery from Porcine Intestinal Mucosa - Anushree Das; Devang P. Khambhati; Niko D. Longoria; Alireza Tabibi; Seyed Mohammad Davachi; Kayli Dimas; Yulianna Laurencin; Lesly Carmona; Pablo Zarate Avalos; Mahmood Karimi Abdolmaleki (Molecules, 2023)
Heparin, a highly sulfated glycosaminoglycan, is a naturally occurring anticoagulant that plays a vital role in various physiological processes. The remarkable structural complexity of heparin, consisting of repeating disaccharide units, makes it a crucial molecule for the development of commercial drugs in the pharmaceutical industry. Over the past few decades, significant progress has been made in the development of cost-effective adsorbents specifically designed for the adsorption of heparin from porcine intestinal mucosa. This advancement has been driven by the need for efficient and scalable methods to extract heparin from natural sources. In this study, we investigated the use of cationic ammonium-functionalized diatomaceous earth, featuring enhanced porosity, larger surface area, and higher thermal stability, to maximize the isolated heparin recovery. Our results showed that the higher cationic density and less bulky quaternary modified diatomaceous earth (QDADE) could adsorb up to 16.3 mg·g−1 (31%) of heparin from the real mucosa samples. Additionally, we explored the conditions of the adsorbent surface for recovery of the heparin molecule and optimized various factors, such as temperature and pH, to optimize the heparin uptake. This is the introductory account of the implementation of modified diatomaceous earth with quaternary amines for heparin capture.